The controversial Christian devotion to Jesus of Nazareth as God - Faria, Lair Amaro dos Santos (Romanitas - Revista de Estudos Grecolatinos, 2015)
Jesus of Nazareth was a simple illiterate Jewish peasant. His followers, however, turned him into God. Given the fact that both Jesus and his followers were monotheists, the carpenter deification demanded intellectual constructions in order to accommodate such ideas without hurting the belief in one God. This study discusses the academic propositions about this change.